2021
DOI: 10.1002/ecm.1454
|View full text |Cite
|
Sign up to set email alerts
|

Solving the fourth‐corner problem: forecasting ecosystem primary production from spatial multispecies trait‐based models

Abstract: Solving the fourth-corner problem: forecasting ecosystem primary production from spatial multispecies trait-based models. Ecological Monographs 00(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 155 publications
(355 reference statements)
0
19
0
1
Order By: Relevance
“…To our knowledge, this is the first formal test of intraspecific variation in trait–environment relationships based on the three‐dimensional performance–trait–environment approach. This evidence adds to that already found across species and communities (Westoby et al ., 2002; Kichenin et al ., 2013; Lajoie & Vellend, 2015; Garnier et al ., 2016; Funk et al ., 2017; Dong et al ., 2020; Buchanan et al ., 2021; Sarker et al ., 2021). Future research could therefore focus on elucidating the origin of this heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first formal test of intraspecific variation in trait–environment relationships based on the three‐dimensional performance–trait–environment approach. This evidence adds to that already found across species and communities (Westoby et al ., 2002; Kichenin et al ., 2013; Lajoie & Vellend, 2015; Garnier et al ., 2016; Funk et al ., 2017; Dong et al ., 2020; Buchanan et al ., 2021; Sarker et al ., 2021). Future research could therefore focus on elucidating the origin of this heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, traits relate to environmental gradients via fundamental eco‐physiological principles that lead to general trait–environment relationships (Westoby et al ., 2002; Garnier et al ., 2016). However, empirical evidence shows differences in trait–environment relationships across communities and regions (Westoby et al ., 2002; Garnier et al ., 2016; Funk et al ., 2017) and also across species found in a region (Kichenin et al ., 2013; Lajoie & Vellend, 2015; Dong et al ., 2020; Buchanan et al ., 2021; Sarker et al ., 2021). This leads to the question of whether trait–environment relationships also vary between genotypes of the same species, for which specific empirical tests are lacking (Westerband et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This step seems to be crucial as intraspecific trait variability and nonlinear environmental trait scaling might heavily influence estimates of ecosystem functioning and multifunctionality (Des Roches et al, 2018; Wong & Carmona, 2021). Recently, Sarker et al (2021) demonstrated the validity of this approach comparing a variety of nonlinear link functions and models to calculate mangrove primary production from variable tree trait expressions. Similar approaches should be used to assess ecosystem service values from trait compositions (Figure 4).…”
Section: Quantifying Functionality and Well‐beingmentioning
confidence: 99%
“…Besides, climate change and sea level rise (SLR) are influencing the growth of many tree species in the Sundarbans (Chowdhury et al, 2016a;Maxwell et al, 2018). Anticipated climate change and SLR may alter population structure and species composition in this ecosystem in future (Ghosh et al, 2019;Sarker et al, 2021). Studying the driving factors behind long-term mangrove growth provides important information on ecosystem functioning and the vulnerability of mangrove species.…”
Section: Introductionmentioning
confidence: 99%